Implementing Dynamic Assessment of Vocabulary Development as a Trialogical Learning Process: A Practice of Teacher Support in Primary Education Schools. Issue 4 (1st October 2016) - van der Veen, Chiel; Dobber, Marjolein; van Oers, Bert
ABSTRACT: Dynamic Assessment (DA) has received a considerable amount of attention in the educational sciences and beyond. DA combines instruction or feedback with assessment or testing within a single activity. DA has great potential for classroom practices, but has not been implemented in many classrooms yet. In this article, we argue that teacher educators play an important role in implementing DA in classrooms. We describe a specific instrument that can be used for dynamically assessing children's vocabulary development in primary school classrooms. We give examples and present some preliminary results of the implementation of this DA instrument based on experiences in primary education schools in the Netherlands. Furthermore, we use the notion of a trialogical learning process to highlight that the collaboration and interaction between teachers and teacher educators are mediated through tools (i.e., DA instruments and materials) that are further developed and may in the end lead to changes in teaching and assessment practices.